5(x-6) - 7(x+2)=-16
Solve the equation 5(x – 6) – 7(x + 2) = –16 for x.
5(x – 6) – 7(x + 2) = –16
5x– 30 –7x –14 = –16
–2x– 44 = –16
–2x = –16 + 44
Our solutions are written by experts, many with advanced degrees, and available 24/7See Solution
Q: hi, how do i solve this by completing the square: x2-1/2x-3/16=0
A: Here a=1, b=-1/2
Q: how do i do a=1/2h(B+b) solve for b
Q: l AT&T LTE 46% 2:14 AM a khanacademy.org Twitter Facebook Email Calculator You might need: Simplify ...
A: We have to factor 45 completely first. 45=3x3x5
Q: If the point (4, −1) is a point on the graph of f, then f(__)=____.
A: (4,-1) is a point on the graph. (x,y)=(4,-1). So at x=4 , y=-1
Q: what is a linear equation?
A: An equation having the highest exponent of variables as 1 is called linear equation.The standard for...
Q: Solve this system of equations by the substitution method. -3x + 5y = 1 x - 2y = -1
Q: Find the slope of the line Y-4=0
A: Click to see the answer
Q: The consumption of a food (in pounds per person) decreased from 10.7 in 1991 to 5.6 in 2007. What wa...
A: Change in time = 2007-1991=16 years
Q: Factoring out a constant before factoring a quadratic. Factor completely 2y2-22y+48 Can someone plea...
Sorry about that. What wasn’t helpful?